Effects of artichoke leaf extract on hepatic ischemia-reperfusion injury - Celepli,Salih (2022)
SUMMARY OBJECTIVE: The aim of this study was to evaluate the hepatoprotective effect and mechanism of action of artichoke leaf extract in hepatic ischemia/reperfusion injury. METHODS: Rats were divided into three groups such as sham, control, and artichoke leaf extract groups. Antioxidant enzyme activities and biochemical parameters were examined from the tissue and serum obtained from the subjects. Histopathological findings were scored semiquantitatively. RESULTS: Statistically, the antioxidant activity was highest in the artichoke leaf extract group, the difference in biochemical parameters and C-reactive protein was significant compared with the control group, and the histopathological positive effects were found to be significantly higher. CONCLUSIONS: As a result, artichoke leaf extract had a hepatoprotective effect and that this effect was related to the antioxidant and anti-inflammatory effects of artichoke.